Cedera Kepala Berat dengan Multiple Open Fracture - Nadia Rizky; Ridwan Kamal; Astri Avianti (Syntax Corporation Indonesia, 2025)
Head injuries are among the most common types of trauma encountered in emergency departments. Many patients with severe brain injuries die before reaching the hospital; data shows that nearly 90% of pre-hospital trauma-related deaths involve brain injuries. Among patients receiving medical care, approximately 75% experience mild brain injuries, 15% moderate, and 10% severe. About 10% of ED patients with head injuries suffer from severe head trauma. Patients with severe head injuries are unable to follow simple commands, even after cardiopulmonary stabilization. These patients are at the highest risk of significant morbidity and mortality. This paper discusses the case of a 21-year-old male diagnosed with severe head injury accompanied by multiple open fractures. Based on the findings, the patient requires emergency management for severe trauma, including craniotomy and debridement. Comprehensive monitoring and evaluation will subsequently be conducted in the intensive care unit. Additionally, the patient and their family will be provided with education regarding the condition to help them understand the potential risks of recurrent injuries.